Provision of Rational Parameters for the Turning Mode of Small-Sized Parts Made of the 29 NK Alloy and Beryllium Bronze for Subsequent Thermal Pulse Deburring; Materials; Vol. 16, iss. 9 - Martyushev N. V. Nikita Vladimirovich; Bublik D. A. Dmitry; Kukartsev V. V. Vladislav Viktorovich; Tynchenko V. S. Vadim Sergeevich; Klyuev R. V. Roman Vladimirovich; Tynchenko Ya. A. Yadviga Aleksandrovna; Karlina Yu. I, Yuliya Igorevna (2023, 2023)
Title screen